ETHICAL AND LEGAL RESPONSIBILITY OF PHYSICIANS FOR MEDICAL ACTIONS THAT POSE A RISK TO PATIENTS (INTERNATIONAL SEMINAR, 2025)
This study aims to describe and analyze the ethical and legal responsibilities of physicians for medical actions that pose risks to patients, focusing on the application of informed consent and triggering factors for legal disputes between patients and doctors. The method used is normative research with a descriptive qualitative approach, based on literature studies of legal documents, medical literature, and professional codes of ethics. Data were systematically analyzed to examine the alignment of legal and ethical norms in risky medical practice. The results of the study show that the ethical responsibility of doctors requires the application of the principles of beneficence and non-maleficence, transparency in the communication of medical risks, and full respect for the autonomy of patients. From a legal perspective, the implementation of Law Number 17 of 2023 concerning Health provides a clear legal umbrella for the protection of patients and doctors, including the obligation of informed consent before medical procedures. However, legal disputes often arise not only due to medical errors, but also due to ineffective communication, unrealistic patient expectations, incomplete documentation, differences in medical interpretation, and psychological factors and hospital management. Thus, fulfilling professional standards accompanied by risk management and good communication can increase patient trust while reducing the potential for legal disputes.